Kombinasi Pemberian Limbah Padat (Sludge) Pabrik Kelapa Sawit dan Pupuk N, P dan K Pada Tanaman Jagung Manis (Zea mays var saccharata Sturt) - Mardani Pradipta; Armain Armain; Al Ikhsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Sweet corn is one of the plants that have a big role in providing the nutritional needs of the community. One effort that can be done to increase the growth and production of sweet corn is fertilization. The purpose of this research is to know the effect of Sludge palm oil mill combination with N, P and K fertilizer on the growth and production of sweet corn and get best treatment from Sludge combination of oil palm factory with N, P and K fertilizer to increase plant growth and production sweet corn. This experiment was conducted experimentally using Randomized Block Design (RAK) consisting of 12 treatments and 3 replications to obtain 36 experimental units. The treatment is a combination of solid waste (Sludge) of oil palm factory with N, P and K (Urea, TSP and KCl) fertilizers. Observation parameters consisted of plant height, stem diameter, female flowering time, harvest age, weight of cobweb and no weight, length of cob, diameter of ear, and production / m2. The result of this research showed that the combination of sludge treatment with N, P and K fertilizer had significant effect on all observation parameters. The best combination of sludge was found in a combination of 15 tons / ha sludge and N, P and K fertilizer (150 kg Urea, 100 kg TSP and 75 kg KCl) / ha. Keywords: Sweet corn, Sludge, N, P and K fertilizer